The Brazilian Holepyris (Hymenoptera, Bethylidae), with description of a new species from Amazonian forest - Gobbi, F. T.; Azevedo, C. O. (Zootaxa, 2006)
The Brazilian fauna of Holepyris is investigated. H. eminentus sp. nov. from Amazonian rain forest is described and illustrated. It is recognized by having large and bulging eyes. New geographic records and taxonomic variation data for H. coriaceus Evans, 1977; H. micidus Evans, 1977; H. subtilis Evans, 1977; H. tenuis Evans, 1977; and H. turrialbae Evans, 1977 are provided. A key to Brazilian species is presented.